2021
DOI: 10.1503/cmaj.202755
|View full text |Cite
|
Sign up to set email alerts
|

Mandatory vaccination for health care workers: an analysis of law and policy

Abstract: Canada will protect both the health workforce and patients, reducing the overall burden of coronavirus disease 2019 on services and ensuring adequate personnel to minister to people's health needs through the pandemic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 7 publications
0
20
0
Order By: Relevance
“…A recent British study found that ethnic minority HCWs, especially the younger females, were negatively associated with uptake of the COVID-19 vaccine [27]. Although challengers argue that HCWs have the right to refuse the vaccination and wear personal protective equipment (PPE) instead, a recent paper analyzing the law and policy of Canadian vaccination for HCWs recommended that governments should put in place policies for mandatory vaccination of all HCWs to reduce the overall burden of COVID-19 [37].…”
Section: Discussionmentioning
confidence: 99%
“…A recent British study found that ethnic minority HCWs, especially the younger females, were negatively associated with uptake of the COVID-19 vaccine [27]. Although challengers argue that HCWs have the right to refuse the vaccination and wear personal protective equipment (PPE) instead, a recent paper analyzing the law and policy of Canadian vaccination for HCWs recommended that governments should put in place policies for mandatory vaccination of all HCWs to reduce the overall burden of COVID-19 [37].…”
Section: Discussionmentioning
confidence: 99%
“…The topic of mandatory vaccinations is a highly charged one. The COVID-19 contagion has presented many scientific, medical, legal, ethical, and policy challenges, and mandatory vaccination programs may well introduce more [36]. The UNESCO International Bioethics Committee (IBC) and the UNESCO World Commission on the Ethics of Scientific Knowledge and Technology (COMEST) recently declared the following:…”
Section: Discussionmentioning
confidence: 99%
“…A central legal justification for exclusion is that unvaccinated people are viewed as being at significant risk of transmitting SARS-CoV-2, which is potentially the most serious externalized risk of the choice to remain unvaccinated. 1 The benefits of vaccination in response to VMVP are clear. Meta-analyses show that SARS-CoV-2 vaccines are effective at reducing the risk of infection, transmission, and severe illness/hospitalization in adults.…”
Section: Introductionmentioning
confidence: 99%
“…A central legal justification for exclusion is that unvaccinated people are viewed as being at significant risk of transmitting SARS-CoV-2, which is potentially the most serious externalized risk of the choice to remain unvaccinated. 1…”
Section: Introductionmentioning
confidence: 99%